Penerapan Konseling Analisis Transaksional dalam Mengatasi Hambatan Komunikasi Lintas Budaya pada Mahasiswa Asal Riau - Bunga Sovia Erik; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study is motivated by the communication barriers experienced by a student from Riau who is studying in West Sumatra and faces difficulties adapting to the Minangkabau cultural environment. Differences in language and communication patterns between the student’s original culture and the surrounding community have caused feelings of insecurity, fear of making mistakes while speaking, and a tendency to withdraw from broader social interactions. Therefore, an in-depth study is needed to understand the dynamics of cross-cultural communication and the counseling strategies used to assist the counselee in the adaptation process. The purpose of this study is to analyze the communication barriers experienced by the counselee and to examine the application of Transactional Analysis counseling in overcoming cross-cultural adaptation problems. The method used is a qualitative descriptive case study approach. Data were collected through observation, interviews, and case analysis, then analyzed descriptively to identify the causes, impacts, and appropriate counseling interventions. The findings of this study indicate that the counselee experienced difficulties in communication due to differences in language, limited understanding of Minangkabau culture, lack of self-confidence, and fear of misunderstanding conversations with older people in the surrounding environment. These conditions led the counselee to interact more frequently with peers from the same cultural background and become less active in wider social settings. Through the Transactional Analysis counseling approach, the counselor helped the counselee recognize ineffective communication patterns and strengthen the Adult ego state to become more rational, calm, and confident in social interactions. The counseling intervention was carried out through communication training, positive reinforcement, cultural understanding, and gradual social adaptation. The results showed positive developments in the counselee’s willingness to learn the Minangkabau language, understand local cultural habits, and begin interacting more actively with the surrounding community.Cross-Cultural Counseling, Transactional Analysis, Communication Barriers